2020
DOI: 10.11113/mjfas.v16n1.1356
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of extreme share return in different Malaysian economic circumstances

Abstract: This study evaluated the performance of probability distribution in various financial periods by investigating the effect of economic cycle on extreme stock return activity. Malaysian stock price KLCI data from 1994–2008 were split into three economy periods correspond to the growth, financial crisis, and the recovery. Four prevalent distributions specifically generalized lambda distribution (GLD), generalized extreme value (GEV), generalized logistic (GLO), and generalized pareto (GPA) were employed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Due to periods of unpredictability and non-random patterns in stock return over the years, the Nigerian stock market's efficiency in the context of emerging markets was evident (Umoru, Udobi-Owoloja, & Nzekwe, 2020). The outcomes are in line with those of the Malaysian stock market in another study by (Marsani & Shabri, 2022), and the Bombay Stock Exchange after dividends announcement (Goyal & Gupta, 2019).…”
Section: Literature Review and Hypothesis Developmentsupporting
confidence: 85%
“…Due to periods of unpredictability and non-random patterns in stock return over the years, the Nigerian stock market's efficiency in the context of emerging markets was evident (Umoru, Udobi-Owoloja, & Nzekwe, 2020). The outcomes are in line with those of the Malaysian stock market in another study by (Marsani & Shabri, 2022), and the Bombay Stock Exchange after dividends announcement (Goyal & Gupta, 2019).…”
Section: Literature Review and Hypothesis Developmentsupporting
confidence: 85%
“…With this, the investment of the portfolio had been common among the investors where the investors tend to benchmark the inflation rate as the required rate of return to invest (Yeoh, 2022). Malaysian stock market exchange on Bursa Malaysia had been referred as one of the biggest stock market exchange in South East Asia (SEA) where the investors tend to be confident in the return on the stock investment (Marsani et al, 2022). Therefore, it is important to assess the market growth rate to explore the possibility for the investors to be on the gaining side against the rising inflation rate over the time (Trihadmini & Falianty, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, market efficiency evaluates how well financial markets consolidate and reflect all available relevant information (El-Diftar, 2024). Accordingly, stock market efficiency refers to the ability of prices to quickly and accurately reflect relevant information, making it impossible for investors to gain unusual returns consistently (Asaad, 2014;Rahimah et al, 2018;Marsani et al, 2022). Market efficiency encompasses three eminent forms: weak, semi-strong, and strong (Garikai Bonga et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies found that stock prices do not follow a random walk (Hawaldar et al, This Journal is licensed under a Creative Commons Attribution 4.0 International License 2017; Ahmed and Hossain, 2019;Houfi, 2019;Al-Faryan and Docker, 2021;Dias et al, 2022). In contrast, others found that the movement of stock prices is unpredictable (Asiedu et al, 2020;Marsani et al, 2022;Zebende et al, 2022). Therefore, the contradiction in the results provides a deep avenue for scientists, researchers, academics, and practitioners to take more interest in this topic and conduct more studies on the subject.…”
Section: Introductionmentioning
confidence: 99%